BANANA PEEL FLAKES ALLEVIATE BLOOD GLUCOSE AND STRESS IN A DOSE-DEPENDENT MANNER - MELIALA, ANDREANYTA; SUMIWI, YUSTINA ANDWI ARI; NARWIDINA, PARAMITA; RINI, SRI LESTARI SULISTYO; SETYANINGSIH, WIDIASTUTI (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Objective: This study aimed to evaluate the antidiabetic and antidepressant effects of banana peel flakes in streptozotocin-induced diabetic rats. Methods: Twenty-five male Wistar rats were classified into five groups with different treatments. Groups I to IV were diabetic rats model groups that consumed only standard diet, standard diet containing 5%, 10%, and 20% of banana peel flakes, respectively. While group V was a healthy control group fed a standard diet. Immunohistochemistry staining was measured to examine serotonin expression in the colon and pancreas. Results: The diabetic rats treated with 20% banana peel flakes had a lower blood glucose concentration (p<0.05) compared with diabetic control and showed a shorter duration of immobility time (p<0.05) than the healthy control. Additionally, compared with diabetic control, the diabetic rats treated with 5% banana peel flakes showed higher serotonin expression (p<0.05) in the colon. In contrast, serotonin expression in the pancreas did not show any significant difference (p>0.05). Conclusion: The present study disclosed that the banana peel flakes provided an antidepressant effect in the diabetic rats model, which might occur through the mechanism of controlling blood glucose concentration.